PERKEMBANGAN PENELITIAN GREEN HOUSING TAHUN 2020-2025: SYSTEMATIC LITERATURE REVIEW MENGGUNAKAN PUBLISH OR PERISH DAN VOSVIEWER - febby asteriani; Ade Wahyudi; rona muliana (LPPM Universitas Abdurrab, 2026)
This research is a systematic study based on Systematic Literature Review (SLR) using a bibliometric approach to map the development of scientific literature on green housing research topics from 2020 to 2025. A total of 100 scientific articles in the form of journals and books were obtained from the Google Scholar database as the main source of data collection. The literature selection process was carried out using Publish or Perish (PoP) software to extract and filter articles based on relevance and citations within the year range and the selection results obtained 90 scientific articles, while network analysis and visualization were carried out using VOSviewer. The main objectives of this study are to map the emergence of keywords (co-occurrence) and bibliometric analysis of collaboration between authors (co-authorship) to identify patterns, trends, and research networks in the field of green housing over the past five years. The results of the co-occurrence analysis produced seven thematic research clusters, namely: technological innovation in the development of environmentally friendly housing, urban green spaces, environmentally friendly housing and consumer preferences, sustainable housing and green architecture, green gentrification, green infrastructure and green innovation. Meanwhile, a bibliometric analysis of co-authorship identified the five most productive and influential authors in the 2020–2025 period. All of these most active researchers were affiliated with academic institutions in China, indicating a lack of cross-border collaboration. These findings provide a comprehensive overview of the current green housing research landscape and can serve as a strategic reference for researchers, practitioners, and policymakers in determining future research directions.